TRANSFORMATION OF TENGKULUK TANDUK WITH WEAVING TECHNIQUES - Sari, Lidia Purnama; Akmal, Ahmad; Dharsono, Dharsono (ISI Press Institut Seni Indonesia Surakarta, 2021)
Tengkuluk is one of the traditional clothing equipment (head cover) of a Bundo Kanduang (biological mother) in the Minangkabau tribe. Currently tengkuluk is rarely used in everyday life, only used in traditional events or other official activities. This reality encourages the creation of this tengkuluk work to be carried out. The method of creating works used consists of three stages, namely experimentation, reflection, and formation. The result of the creation of this work shows that the tengkuluk made with woven techniques and pandan leaf material and decorated with Swarovski looks practical and flexible when used by mothers and teenagers in their daily lives. This new creation in the form of the Koto Gadang tengkuluk expresses the meaning of philosophical values, namely the responsibility of women when they have married.